In-situ interface bonding graphene ultrafine copper bonding wire and preparation method thereof

CN122913504APending Publication Date: 2026-10-16ZHEJIANG HUAJU NEW MATERIAL TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611336349.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]例如公告号为 CN112359244A 的发明专利公开了一种高强高导石墨烯铜复合线材及其制备方法,采用混粉-冷等静压-真空烧结-热挤压-连续挤压-拉拔的工艺方法,由于铜粉、石墨烯直接共混,石墨烯不仅极易团聚,而且会引入大量孔隙,两相无界面键合,仅靠物理结合、界面结合力弱,不仅造成石墨烯铜复合线材抗拉强度提升有限、易断裂,还会增大界面接触电阻、割裂导电通路,导致产品强度不足、导电率偏低且性能稳定性差

Benefits of technology

本发明中,先对石墨烯进行原位羟基化改性处理,在石墨烯表面原位生成羟基,提高与铜粉润湿性与分散性,然后对其进行纳米碳点修饰,对石墨烯进行微量纳米碳点修饰,实现石墨烯与后续复合铜纳米片表面的碳纳米颗粒形成原位碳-碳共价连接,在层间堆叠界面构建密集碳桥,让石墨烯与复合铜纳米片从 “贴合堆叠” 变为 “整体键合”,不仅大幅提升层间载荷传递效率,而且显著提升二者间的结合强度,从而有助于显著提升铜键合丝的抗拉强度与结构整体性;然后以二水合氯化铜作为铜源,与氨水发生铜氨络合,经水浴反应合成碱式氧化铜纳米片前驱体,经洗涤干燥后,在氩气气氛中,低温氢气还原造孔,从而得到多孔铜纳米片,再以 D-葡萄糖作为碳源,将多孔铜纳米片加入到碳源溶液中,经水热反应,D-葡萄糖缓慢脱水碳化,在多孔铜纳米片表面及介孔内部生成碳纳米颗粒,实现原位锚定,并且通过退火处理,可进一步固化碳颗粒与多孔铜纳米片基体的界面结合,消除残余有机基团,从而有利于提升后续与石墨烯的层间结合稳定性;通过将纳米碳点修饰处理的石墨烯、复合铜纳米片以及铜粉进行混合,碳纳米颗粒预先沉积在多孔铜纳米片表面,可以起到隔离位点作用,阻止石墨烯片层团聚,使得石墨烯连续性更好,并且复合铜纳米片与石墨烯定向层状堆叠,形成类似 “层状复合板材” 的受力结构,在外力作用下,层间界面可偏转裂纹、延长裂纹扩展路径,纳米片层间的机械嵌插,可以实现载荷高效传递,而且复合铜纳米片上沉积的碳纳米颗粒与石墨烯之间形成原位碳-碳共价连接,使得石墨烯与复合铜纳米片层间紧密贴合,界面不易脱粘、滑移,复合体系整体协同承载能力大幅提高,从而可以显著提升铜键合丝的抗拉强度;同时,复合铜纳米片中的多孔铜纳米片基体作为二维导电骨架,可以层间堆叠形成连续铜导电通路,水热沉积的碳纳米颗粒,以及石墨烯均为高导电碳材料,在铜片层间搭建跨层导电通道,不仅可以弥补铜基体晶界、孔隙带来的导电损耗,而且有序层状结构让导电相定向排布,电流传输方向更顺畅,从而使得铜键合丝的导电效果更好。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_12
    Figure SMS_12
Patent Text Reader

Abstract

The application discloses in-situ interface bonding graphene superfine copper bonding wire and a preparation method thereof, comprising the following steps: 1) graphene in-situ hydroxylation modification and dispersion; 2) vacuum low-temperature degassing and powder mixing; 3) cold isostatic pressing; 4) low-temperature vacuum pre-burning; 5) gradient hot isostatic pressing densification; 6) medium-low temperature hot extrusion; 7) multi-pass controlled drawing; and 8) stepwise low-temperature annealing. In the application, the graphene is subjected to hydroxylation treatment and nanometer carbon point modification treatment, and is mixed with composite copper nanosheet and copper powder, the composite copper nanosheet and the graphene construct an ordered interlayer intercalation and stacking in-situ bonding structure, the C-C, Cu-O-C multiple chemical bonding and the interlayer mechanical interlocking effect are relied on to strengthen the interface bonding, optimize the load transmission and passivate the crack propagation, meanwhile, the regular multi-stage conductive network greatly reduces the interface contact resistance and the grain boundary resistance, and the tensile strength and the conductivity of the copper bonding wire are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microelectronic packaging interconnect materials technology, specifically to an in-situ interface-bonded graphene ultrafine copper bonding wire and its preparation method. Background Technology

[0002] Copper-based wires are widely used in electronic devices due to their high conductivity and good processing performance. However, the mechanical properties and conductivity of traditional copper-based wires have reached their limits, restricting their further application in circuits, new energy vehicles, and high-power cables. Graphene is a two-dimensional layered nanomaterial with a hexagonal lattice structure formed by carbon atoms bonded through sp² hybrid orbitals. Due to its high thermal conductivity, high carrier mobility, high specific surface area, and high strength, it has become an ideal reinforcing phase for copper-based composite materials. Introducing graphene as a reinforcing phase into a copper matrix is ​​expected to achieve higher strength while maintaining the high conductivity of the copper matrix.

[0003] For example, the invention patent with announcement number CN112359244A discloses a high-strength, high-conductivity graphene-copper composite wire and its preparation method. The process involves mixing powder, cold isostatic pressing, vacuum sintering, hot extrusion, continuous extrusion, and drawing. Because copper powder and graphene are directly blended, graphene is not only prone to agglomeration, but also introduces a large number of pores. The two phases have no interfacial bonding and rely solely on physical bonding, resulting in weak interfacial bonding. This not only limits the improvement of tensile strength and makes the graphene-copper composite wire prone to breakage, but also increases interfacial contact resistance and severs conductive pathways, leading to insufficient product strength, low conductivity, and poor performance stability. Summary of the Invention

[0004] To address the problems existing in the prior art, the purpose of this invention is to provide an in-situ interface-bonded graphene ultrafine copper bonding wire and its preparation method.

[0005] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire includes the following steps: 1) In-situ hydroxylation modification and dispersion of graphene: Hydroxyl groups are generated in situ on the surface of graphene, which improves the wettability and dispersibility when mixed with copper powder. 2) Hydroxylated graphene is modified with carbon nanodots. A small amount of carbon nanodots are used to modify the graphene to achieve carbon-carbon homogeneous bonding between the graphene and the subsequent composite copper nanosheets, completely eliminating the shortcomings of the carbon-copper heterogeneous interface. Then, it is mixed with composite copper nanosheets and copper powder at a mass ratio of (0.05-0.2):(0.05-0.2):100, and vacuum low temperature degassing is performed to remove moisture and adsorbed gas, making the mixing more uniform. 3) Cold isostatic pressing: pressing the mixed powder into a dense blank; 4) Low-temperature vacuum pre-firing allows for initial diffusion bonding between powder particles, improving the strength of the green body; 5) Gradient hot isostatic pressing densification completely closes the internal pores, and graphene and copper form in-situ interface bonds, while keeping the graphene from decomposing at high temperatures. 6) Low-temperature hot extrusion extrudes the dense billet into bars, further densifying and fibrousizing it, providing a microstructure basis for drawing; 7) Multi-pass controlled drawing, drawing from a coarse bar to an ultra-fine bonded wire, controlling the reduction rate of the drawing surface in a single pass to avoid wire breakage; 8) Stepped low-temperature annealing eliminates tensile stress, restores plasticity, and strengthens the graphene-copper in-situ interface bonding, thereby improving conductivity and strength.

[0006] As a further preferred embodiment of the present invention, the specific operations for the in-situ hydroxylation modification and dispersion of graphene are as follows: Graphene is added to a mixed solvent of equal volumes of deionized water and anhydrous ethanol and ultrasonically dispersed at 400-600W for 60-80 minutes to obtain a dispersion of 1-3 mg / mL. Then, saturated ammonia is slowly added dropwise to adjust the pH to 9-10. The mixture is stirred at 300-500 rpm for 2-4 hours in a constant temperature water bath at 60-70℃. After cooling to room temperature, the mixture is centrifuged, washed, dried, and then ground through a 300-500 mesh sieve.

[0007] As a further preferred embodiment of the present invention, the specific operation of modifying the hydroxylated graphene with nano-carbon dots is as follows: Water-soluble carbon dot powder with a particle size of 3-5 nm was added to deionized water and uniformly dispersed to obtain a carbon dot dispersion with a concentration of 0.02-0.05 mg / mL. Then, hydroxylated graphene was added to the carbon dot dispersion according to a mass ratio of graphene to water-soluble carbon dots of 100:(0.3-0.5). The dispersion was ultrasonically dispersed at 300-400 W for 20-30 min, then allowed to stand at room temperature for 10-20 min, and finally dried under vacuum.

[0008] As a further preferred embodiment of the present invention, the method for preparing the composite copper nanosheets is as follows: 1) Add D-glucose and polyethylene glycol-4000 to deionized water and stir thoroughly at room temperature to dissolve them, thereby obtaining a carbon source solution. Then add porous copper nanosheets to the carbon source solution and ultrasonically disperse for 50-80 minutes to obtain a suspension. 2) Transfer the suspension to a hydrothermal reactor, seal it, and hydrothermally react for 18-24 hours. After the reaction is complete, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, dry it, and place it in a tube furnace. Treat it at a constant temperature for 1-2 hours under the protection of high-purity argon. After the treatment is complete, cool it to room temperature with the furnace to obtain composite copper nanosheets.

[0009] Furthermore, the ratio of D-glucose, polyethylene glycol-4000, deionized water, and porous copper nanosheets is (1.5-2.5) g : (0.05-0.10) g : (100-200) mL : (0.2-0.5) g; The power of the ultrasonic dispersion is 300-400W; The temperature of the hydrothermal reaction is 170-180℃; The temperature for the isothermal treatment is 250-280℃.

[0010] As a further preferred embodiment of the present invention, the method for preparing the porous copper nanosheets is as follows: 1) Add copper chloride dihydrate and polyethylene glycol-4000 to deionized water, stir thoroughly at room temperature until completely dissolved, slowly add saturated ammonia water, adjust the pH value to 9.5-10.0, and continue stirring at 150-200 r / min for 30-50 min to obtain the precursor solution; 2) Heat the precursor solution to 85-90℃, and slowly add sodium hydroxide solution dropwise while stirring at 100-150r / min to adjust the pH value to 11.5-12.0. Keep it at a constant temperature for 2-5h, and after naturally cooling to room temperature, filter and collect the precipitate. Wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain copper oxide nanosheet powder. 3) Spread copper oxide nanosheets evenly in a ceramic boat, place it in a tube furnace, purge the air with high-purity argon gas, and then... In a reducing mixture, the temperature is raised to 300-320℃ and held at that temperature for 2-5 hours. After the holding period, the hydrogen gas is turned off, and the furnace is cooled to room temperature under argon protection to obtain porous copper nanosheets.

[0011] Furthermore, in the precursor solution, the ratio of copper chloride dihydrate, polyethylene glycol-4000, and deionized water is (1-3) g: (2-5) g: (500-1000) mL; The concentration of the sodium hydroxide solution is 2.0-2.5 mol / L; The The hydrogen volume content in the reducing mixture is 5-8%; The heating rate is 2-3℃ / min.

[0012] As a further preferred embodiment of the present invention, the specific operation steps of the vacuum low-temperature degassing and powder mixing are as follows: first, vacuum pump to ≤ Hold at 80-120℃ for 2-5 hours to remove gas, then fill with high-purity argon to positive pressure and mix the powder at 10-30 rpm for 12-24 hours. The conditions for cold isostatic pressing are: pressure 200-400MPa, holding pressure for 5-15min; As a further preferred embodiment of the present invention, the specific operation of the gradient hot isostatic pressing densification is as follows: under the protection of high-purity argon, first hold at 300-350℃ and 50-80MPa for 30-50min, then hold at 500-550℃ and 100-150MPa for 60-80min, and finally hold at 680-720℃ and 150-200MPa for 80-120min; The specific operation of the medium and low temperature hot extrusion is as follows: under high purity pressure protection, preheat at 500-600℃ for 30-50 minutes, and then extrude at 400-500℃ with an extrusion ratio of (10-20):1, with an extrusion outlet bar diameter of 5-10mm. The specific operation of the multi-pass controlled drawing is as follows: the single-pass reduction rate of the drawing is 10-15%, first coarse drawing to a diameter of 1-2 mm, then medium drawing to a diameter of 0.2-0.5 mm, and finally fine drawing to a diameter of 15-30 μm; The specific operation of the stepped low-temperature annealing is as follows: under the protection of high-purity argon, first hold at 150-200℃ for 30-50 min, then hold at 250-300℃ for 60-100 min, and finally hold at 180-220℃ for 30-50 min.

[0013] An in-situ interfacial bonded graphene ultrafine copper bonding wire was prepared using the above-described preparation method.

[0014] Compared with the prior art, the beneficial effects of the present invention are: In this invention, graphene is first modified by in-situ hydroxylation to generate hydroxyl groups on its surface, improving its wettability and dispersibility with copper powder. Then, it is modified with nano-carbon dots to achieve in-situ carbon-carbon covalent bonding between the graphene and the carbon nanoparticles on the surface of the subsequent composite copper nanosheets. This creates dense carbon bridges at the interlayer stacking interface, allowing the graphene and the composite copper nanosheets to achieve a seamless, "stacked" connection. The process transforms the copper bonding wire into a "monolithic bond," significantly improving not only the interlayer load transfer efficiency but also the bonding strength between the two layers. This, in turn, helps to significantly enhance the tensile strength and structural integrity of the copper bonding wire. Then, using copper chloride dihydrate as the copper source, a copper-ammonia complex is formed with ammonia water, and a basic copper oxide nanosheet precursor is synthesized via a water bath reaction. After washing and drying, the precursor is pore-forming via low-temperature hydrogen reduction in an argon atmosphere, resulting in porous copper nanosheets. Finally, using D-glucose as the carbon source, the porous copper nanosheets are added to the carbon source solution. Through a hydrothermal reaction, D-glucose slowly dehydrates and carbonizes, forming carbon on the surface of the porous copper nanosheets. Carbon nanoparticles are generated within the mesopores, achieving in-situ anchoring. Annealing further solidifies the interfacial bond between the carbon particles and the porous copper nanosheet matrix, eliminating residual organic groups and thus improving the stability of the subsequent interlayer bonding with graphene. By mixing graphene modified with carbon nanoparticles, composite copper nanosheets, and copper powder, the carbon nanoparticles are pre-deposited on the surface of the porous copper nanosheets, acting as isolation sites to prevent graphene sheet aggregation and improve graphene continuity. Furthermore, the composite copper nanosheets and graphene are stacked in oriented layers, forming a layered composite substrate-like structure. Under external force, the interlayer interface of the composite copper nanosheets can deflect cracks and extend crack propagation paths. The mechanical interlocking between nanosheet layers enables efficient load transfer. Furthermore, the carbon nanoparticles deposited on the composite copper nanosheets form in-situ carbon-carbon covalent bonds with graphene, resulting in a tight bond between the graphene and the composite copper nanosheets. The interface is not prone to debonding or slippage, significantly improving the overall synergistic load-bearing capacity of the composite system and thus significantly enhancing the tensile strength of the copper bonding wire. At the same time, the porous copper nanosheet matrix in the composite copper nanosheets serves as a two-dimensional conductive framework, which can be stacked between layers to form continuous copper conductive pathways. The hydrothermally deposited carbon nanoparticles and graphene are both highly conductive carbon materials. Building interlayer conductive channels between copper sheets not only compensates for the conductive losses caused by the grain boundaries and pores of the copper matrix, but also allows the conductive phases to be oriented in an orderly layered structure, making the current transmission direction smoother and thus improving the conductivity of the copper bonding wire.

[0015] In this invention, graphene is hydroxylated and modified with nano-carbon dots, then mixed with composite copper nanosheets and copper powder. The composite copper nanosheets and graphene construct an ordered interlayer intercalation stacked in-situ bonded structure, which can effectively avoid graphene agglomeration and matrix pore defects. Relying on the multiple chemical bonds of CC and Cu-OC and the interlayer mechanical interlocking effect, the interface bonding is strengthened, the load transfer is optimized, and the crack propagation is passively blocked, which significantly improves the tensile strength of the copper bonded wire. At the same time, the regular and dense multi-level conductive network greatly reduces the interface contact resistance and grain boundary resistance, so as to achieve a simultaneous improvement in the tensile strength and conductivity of the copper bonded wire, resulting in better overall performance and service stability. Detailed Implementation

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Example 1 A method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire includes the following steps: S1. Graphene was added to a mixed solvent of equal volumes of deionized water and anhydrous ethanol and dispersed by ultrasonication at 400W for 60 min to obtain a 1 mg / mL dispersion. Then, saturated ammonia was slowly added dropwise to adjust the pH to 9. The mixture was stirred at 300 r / min for 2 h in a constant temperature water bath at 60℃. After cooling to room temperature, it was centrifuged, washed, dried, and ground through a 300-mesh sieve to obtain hydroxylated graphene.

[0018] S2. Water-soluble carbon dot powder with a particle size of 3 nm was added to deionized water and uniformly dispersed to obtain a carbon dot dispersion with a concentration of 0.02 mg / mL. Then, hydroxylated graphene was added to the carbon dot dispersion at a mass ratio of graphene to water-soluble carbon dots of 100:0.3. The dispersion was ultrasonically dispersed at 300 W for 20 min, then allowed to stand at room temperature for 10 min, and finally vacuum dried to obtain nano-carbon dot-modified hydroxylated graphene. This was then mixed with composite copper nanosheets and copper powder at a mass ratio of 0.05:0.05:100 and degassed under vacuum at low temperature. The vacuum was first evacuated to ≤ The mixture was kept at 80℃ for 2 hours to remove gas, and then high-purity argon gas was introduced to positive pressure. The mixture was then mixed with powder at 10 rpm for 12 hours. S3 involves cold isostatic pressing of the mixed powder at 200 MPa for 5 minutes, followed by low-temperature vacuum pre-firing at 500℃ and vacuum ≤ Heat for 2 hours to obtain the green body; S4 The billet is densified by gradient hot isostatic pressing. Under the protection of high-purity argon, it is first held at 300℃ and 50MPa for 30min, then at 500℃ and 100MPa for 60min, and finally at 680℃ and 150MPa for 80min. Then, it is subjected to medium and low temperature hot extrusion. Under the protection of high-purity pressure, it is preheated at 500℃ for 30min, and then extruded at 400℃ and extrusion ratio of 10:1. The diameter of the extruded bar is 5mm, and the bar is obtained. S5 involves multiple controlled drawing passes of the bar stock, with a single pass reducing the surface area by 10%. The stock is first coarsely drawn to a diameter of 1 mm, then intermediately drawn to a diameter of 0.2 mm, and finally finely drawn to a diameter of 15 μm to obtain a semi-finished ultrafine bonding wire. This semi-finished wire is then subjected to a stepped low-temperature annealing treatment. Under the protection of high-purity argon, the wire is first held at 150°C for 30 min, then at 250°C for 60 min, and finally at 180°C for 30 min to obtain the finished bonding wire.

[0019] The preparation method of the composite copper nanosheets is as follows: 1) Add 1g of copper chloride dihydrate and 2g of polyethylene glycol-4000 to 500mL of deionized water, stir thoroughly at room temperature until completely dissolved, slowly add saturated ammonia water, adjust the pH value to 9.5, and continue stirring at 150r / min for 30min to obtain the precursor solution; 2) Heat the precursor solution to 85℃, slowly add 2mol / L sodium hydroxide solution dropwise while stirring at 100r / min, adjust the pH value to 11.5, keep it at a constant temperature for 2h, cool it naturally to room temperature, filter and collect the precipitate, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain copper oxide nanosheet powder. 3) Copper oxide nanosheets were evenly spread in a ceramic boat, placed in a tube furnace, and high-purity argon gas was introduced to purge the air. Then, hydrogen gas with a volume content of 5% was introduced. In a reducing mixture, the temperature is increased to 300℃ at a rate of 2℃ / min, and held at that temperature for 2 hours. After the holding period, the hydrogen gas is turned off, and the furnace is cooled to room temperature under argon protection to obtain porous copper nanosheets. 4) Add 1.5g D-glucose and 0.05g polyethylene glycol-4000 to 100mL deionized water and stir thoroughly at room temperature to dissolve them, thus obtaining a carbon source solution. Then add 0.2g porous copper nanosheets to the carbon source solution and disperse by ultrasonication at 300W for 50min to obtain a suspension. 5) Transfer the suspension to a hydrothermal reactor, seal it, and hydrothermally react at 170°C for 18 hours. After the reaction is complete, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, dry it, and place it in a tube furnace. Under the protection of high-purity argon, treat it at 250°C for 1 hour. After the treatment is complete, cool it to room temperature with the furnace to obtain composite copper nanosheets.

[0020] Example 2 A method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire includes the following steps: S1. Graphene was added to a mixed solvent of equal volumes of deionized water and anhydrous ethanol and dispersed by ultrasonication at 500W for 70 min to obtain a dispersion of 2 mg / mL. Then, saturated ammonia was slowly added dropwise to adjust the pH value to 9.5. The mixture was stirred at 400 r / min for 3 h in a constant temperature water bath at 65℃. After cooling to room temperature, it was centrifuged, washed, dried, and ground through a 400-mesh sieve to obtain hydroxylated graphene. S2. Water-soluble carbon dot powder with a particle size of 4 nm was added to deionized water and uniformly dispersed to obtain a carbon dot dispersion with a concentration of 0.03 mg / mL. Then, hydroxylated graphene was added to the carbon dot dispersion at a mass ratio of graphene to water-soluble carbon dots of 100:0.4. The dispersion was ultrasonically dispersed at 400 W for 25 min, then allowed to stand at room temperature for 15 min, and finally vacuum dried to obtain nano-carbon dot-modified hydroxylated graphene. This was then mixed with composite copper nanosheets and copper powder at a mass ratio of 0.1:0.12:100 and degassed under vacuum at low temperature. The vacuum was first evacuated to ≤ The gas was degassed at 100℃ for 3 hours, then high-purity argon was introduced to positive pressure, and the powder was mixed at 20 rpm for 18 hours. S3 The mixed powder is cold isostatically pressed into shape at a pressure of 300MPa for 10 minutes, and then subjected to low-temperature vacuum pre-firing at a temperature of 540℃ and a vacuum of ≤5×10⁻³Pa for 3 hours to obtain the green body; S4 The billet is densified by gradient hot isostatic pressing. Under the protection of high-purity argon, it is first held at 320℃ and 65MPa for 40min, then at 520℃ and 120MPa for 70min, and finally at 700℃ and 180MPa for 100min. Then, it is subjected to medium and low temperature hot extrusion. Under the protection of high-purity pressure, it is preheated at 550℃ for 40min, and then extruded at 450℃ and extrusion ratio of 15:1. The diameter of the extruded bar is 8mm, and the bar is obtained. S5 involves multiple controlled drawing passes of the bar stock, with a single pass reducing the surface area by 12%. The stock is first coarsely drawn to a diameter of 1.5 mm, then intermediately drawn to a diameter of 0.3 mm, and finally finely drawn to a diameter of 25 μm to obtain a semi-finished ultrafine bonding wire. This semi-finished wire is then subjected to a stepped low-temperature annealing treatment. Under the protection of high-purity argon, the wire is first held at 180°C for 40 min, then at 280°C for 80 min, and finally at 200°C for 40 min to obtain the finished bonding wire.

[0021] The preparation method of the composite copper nanosheets is as follows: 1) Add 2g of copper chloride dihydrate and 3g of polyethylene glycol-4000 to 800mL of deionized water, stir thoroughly at room temperature until completely dissolved, slowly add saturated ammonia water to adjust the pH value to 10.0, and continue stirring at 180r / min for 40min to obtain the precursor solution; 2) Heat the precursor solution to 86℃, slowly add 2.3mol / L sodium hydroxide solution dropwise while stirring at 120r / min, adjust the pH value to 12.0, keep it at a constant temperature for 3h, and after naturally cooling to room temperature, filter and collect the precipitate, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain copper oxide nanosheet powder. 3) Copper oxide nanosheets were evenly spread in a ceramic boat, placed in a tube furnace, and high-purity argon gas was introduced to purge the air. Then, in a furnace with a hydrogen volume content of 7%, the nanosheets were evenly spread in a ceramic boat. In a reducing mixture, the temperature is increased to 310℃ at a rate of 3℃ / min, and held at that temperature for 3 hours. After the holding period, the hydrogen gas is turned off, and the furnace is cooled to room temperature under argon protection to obtain porous copper nanosheets. 4) Add 2g D-glucose and 0.08g polyethylene glycol-4000 to 150mL deionized water and stir thoroughly at room temperature to dissolve and obtain a carbon source solution. Then add 0.3g porous copper nanosheets to the carbon source solution and disperse by ultrasonication at 350W for 60min to obtain a suspension. 5) Transfer the suspension to a hydrothermal reactor, seal it, and hydrothermally react at 175°C for 20 hours. After the reaction is complete, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, dry it, and place it in a tube furnace. Under the protection of high-purity argon, treat it at 270°C for 2 hours. After the treatment is complete, cool it to room temperature with the furnace to obtain composite copper nanosheets.

[0022] Example 3 A method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire includes the following steps: S1 In-situ hydroxylation modification and dispersion of graphene: Graphene was added to a mixed solvent of equal volumes of deionized water and anhydrous ethanol, and ultrasonically dispersed at 600W for 80 min to obtain a dispersion of 3 mg / mL. Then, saturated ammonia was slowly added dropwise to adjust the pH value to 10. The mixture was stirred at 500 r / min for 4 h in a constant temperature water bath at 70℃. After cooling to room temperature, the mixture was centrifuged, washed, dried, and ground through a 500-mesh sieve to obtain hydroxylated graphene. S2. Water-soluble carbon dot powder with a particle size of 5 nm was added to deionized water and uniformly dispersed to obtain a carbon dot dispersion with a concentration of 0.05 mg / mL. Then, hydroxylated graphene was added to the carbon dot dispersion at a mass ratio of graphene to water-soluble carbon dots of 100:0.5. The dispersion was ultrasonically dispersed at 400 W for 30 min, then allowed to stand at room temperature for 20 min, and finally vacuum dried to obtain nano-carbon dot-modified hydroxylated graphene. This was then mixed with composite copper nanosheets and copper powder at a mass ratio of 0.2:0.2:100 and degassed under vacuum at low temperature. The vacuum was first evacuated to ≤ The mixture was kept at 120℃ for 5 hours to remove gas, then high-purity argon was introduced to positive pressure, and the powder was mixed at 30 rpm for 24 hours. S3 involves cold isostatic pressing of the mixed powder at 400 MPa for 15 minutes, followed by low-temperature vacuum pre-firing at 580°C. The green body is obtained by heat preservation for 5 hours; S4 The billet is densified by gradient hot isostatic pressing. Under the protection of high-purity argon, it is first held at 350℃ and 80MPa for 50min, then at 550℃ and 150MPa for 80min, and finally at 720℃ and 200MPa for 120min. Then, it is subjected to medium and low temperature hot extrusion. Under the protection of high-purity pressure, it is preheated at 600℃ for 50min, and then extruded at 500℃ and extrusion ratio of 20:1. The diameter of the extruded bar is 10mm, and the bar is obtained. S5 involves multiple controlled drawing passes of the bar stock, with a single pass reducing the surface area by 15%. The stock is first coarsely drawn to a diameter of 2 mm, then intermediately drawn to a diameter of 0.5 mm, and finally finely drawn to a diameter of 30 μm to obtain a semi-finished ultrafine bonding wire. This semi-finished wire is then subjected to a stepped low-temperature annealing treatment. Under the protection of high-purity argon, the wire is first held at 200°C for 50 min, then at 300°C for 100 min, and finally at 220°C for 50 min to obtain the finished bonding wire.

[0023] The preparation method of the composite copper nanosheets is as follows: 1) Add 3g of copper chloride dihydrate and 5g of polyethylene glycol-4000 to 1000mL of deionized water, stir thoroughly at room temperature until completely dissolved, slowly add saturated ammonia water, adjust the pH value to 10.0, and continue stirring at 200r / min for 50min to obtain the precursor solution; 2) Heat the precursor solution to 90℃, slowly add 2.5mol / L sodium hydroxide solution dropwise while stirring at 150r / min, adjust the pH value to 12.0, keep it at a constant temperature for 5h, and after naturally cooling to room temperature, filter and collect the precipitate, wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain copper oxide nanosheet powder. 3) Copper oxide nanosheets were evenly spread in a ceramic boat, placed in a tube furnace, and high-purity argon gas was introduced to purge the air. Then, hydrogen gas with a volume content of 8% was introduced. In a reducing mixture, the temperature is increased to 320℃ at a rate of 3℃ / min, and held at that temperature for 5 hours. After the holding period, the hydrogen gas is turned off, and the furnace is cooled to room temperature under argon protection to obtain porous copper nanosheets. 4) Add 2.5g D-glucose and 0.10g polyethylene glycol-4000 to 200mL deionized water and stir thoroughly at room temperature to dissolve them, thus obtaining a carbon source solution. Then add 0.5g porous copper nanosheets to the carbon source solution and disperse by ultrasonication at 400W for 80min to obtain a suspension. 5) Transfer the suspension to a hydrothermal reactor, seal it, and hydrothermally react at 180°C for 24 hours. After the reaction is complete, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, dry it, and place it in a tube furnace. Under the protection of high-purity argon, treat it at a constant temperature of 280°C for 2 hours. After the treatment is complete, cool it to room temperature with the furnace to obtain composite copper nanosheets.

[0024] Comparative Example 1: This comparative example is basically the same as Example 1, except that the hydroxylation modification treatment is omitted in S1.

[0025] Comparative Example 2: This comparative example is basically the same as Example 1, except that the nano carbon dot modification treatment is omitted in S1.

[0026] Comparative Example 3: This comparative example is basically the same as Example 1, except that the composite copper nanosheets are omitted in S1.

[0027] Comparative Example 4: This comparative example is basically the same as Example 1, except that copper nanosheets are used instead of porous copper nanosheets in the preparation of composite copper nanosheets.

[0028] Comparative Example 5: This comparative example is basically the same as Example 1, except that steps 4)-5) are omitted in the preparation of the composite copper nanosheets.

[0029] Test Experiment Ultrafine copper bonding wire samples were processed using the methods described in Examples 1-3 and Comparative Examples 1-5, and their performance was tested. The tensile strength was tested using an Instron 3369 electronic universal testing machine at a tensile speed of 15 mm / min. The conductivity was measured using a HIOKI double-arm bridge resistance meter. Each sample was tested three times, and the average value of the results was calculated. The results are shown in Table 1.

[0030] Table 1

[0031] As shown in Table 1, the ultrafine copper bonding wire obtained in this invention has a tensile strength of over 600 MPa and a conductivity of over 107% IACS, combining high strength and high conductivity, and exhibiting superior overall performance and service stability.

[0032] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire, characterized in that, Includes the following steps: 1) In-situ hydroxylation modification and dispersion of graphene; 2) Hydroxylated graphene was modified with carbon nanoparticles and then mixed with composite copper nanosheets and copper powder in a mass ratio of (0.05-0.2):(0.05-0.2):100 under vacuum and low temperature degassing. 3) Cold isostatic pressing; 4) Low-temperature vacuum pre-firing; 5) Gradient hot isostatic pressing densification; 6) Medium and low temperature hot extrusion; 7) Multi-stage controlled pulling; 8) Stepped low-temperature annealing.

2. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 1, characterized in that, The specific operations for the in-situ hydroxylation modification and dispersion of graphene are as follows: Graphene is added to a mixed solvent of equal volumes of deionized water and anhydrous ethanol and ultrasonically dispersed at 400-600W for 60-80 minutes to obtain a dispersion of 1-3 mg / mL. Then, saturated ammonia is slowly added dropwise to adjust the pH to 9-10. The mixture is stirred at 300-500 rpm for 2-4 hours in a constant temperature water bath at 60-70℃. After cooling to room temperature, the mixture is centrifuged, washed, dried, and then ground through a 300-500 mesh sieve.

3. The method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 1, characterized in that, The specific steps for modifying the hydroxylated graphene with nano-carbon dots are as follows: Water-soluble carbon dot powder with a particle size of 3-5 nm was added to deionized water and uniformly dispersed to obtain a carbon dot dispersion with a concentration of 0.02-0.05 mg / mL. Then, hydroxylated graphene was added to the carbon dot dispersion according to a mass ratio of graphene to water-soluble carbon dots of 100:(0.3-0.5). The dispersion was ultrasonically dispersed at 300-400 W for 20-30 min, then allowed to stand at room temperature for 10-20 min, and finally dried under vacuum.

4. The method for preparing in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 1, characterized in that, The method for preparing the composite copper nanosheets is as follows: 1) Add D-glucose and polyethylene glycol-4000 to deionized water and stir thoroughly at room temperature to dissolve them, thereby obtaining a carbon source solution. Then add porous copper nanosheets to the carbon source solution and ultrasonically disperse for 50-80 minutes to obtain a suspension. 2) Transfer the suspension to a hydrothermal reactor, seal it, and hydrothermally react for 18-24 hours. After the reaction is complete, allow it to cool naturally to room temperature. After centrifugation, wash it repeatedly with deionized water and anhydrous ethanol, dry it, and place it in a tube furnace. Treat it at a constant temperature for 1-2 hours under the protection of high-purity argon. After the treatment is complete, cool it to room temperature with the furnace to obtain composite copper nanosheets.

5. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 4, characterized in that, The ratio of D-glucose, polyethylene glycol-4000, deionized water, and porous copper nanosheets is (1.5-2.5) g : (0.05-0.10) g : (100-200) mL : (0.2-0.5) g; The power of the ultrasonic dispersion is 300-400W; The temperature of the hydrothermal reaction is 170-180℃; The temperature for the isothermal treatment is 250-280℃.

6. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 4, characterized in that, The porous copper nanosheets are prepared as follows: 1) Add copper chloride dihydrate and polyethylene glycol-4000 to deionized water, stir thoroughly at room temperature until completely dissolved, slowly add saturated ammonia water, adjust the pH value to 9.5-10.0, and continue stirring at 150-200 r / min for 30-50 min to obtain the precursor solution; 2) Heat the precursor solution to 85-90℃, and slowly add sodium hydroxide solution dropwise while stirring at 100-150r / min to adjust the pH value to 11.5-12.

0. Keep it at a constant temperature for 2-5h, and after naturally cooling to room temperature, filter and collect the precipitate. Wash it repeatedly with deionized water and anhydrous ethanol, and dry it to obtain copper oxide nanosheet powder. 3) Spread copper oxide nanosheets evenly in a ceramic boat, place it in a tube furnace, purge the air with high-purity argon gas, and then... In a reducing mixture, the temperature is raised to 300-320℃ and held at that temperature for 2-5 hours. After the holding period, the hydrogen gas is turned off, and the furnace is cooled to room temperature under argon protection to obtain porous copper nanosheets.

7. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 6, characterized in that, In the precursor solution, the ratio of copper chloride dihydrate, polyethylene glycol-4000, and deionized water is (1-3) g: (2-5) g: (500-1000) mL. The concentration of the sodium hydroxide solution is 2.0-2.5 mol / L; The The hydrogen volume content in the reducing mixture is 5-8%; The heating rate is 2-3℃ / min.

8. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 1, characterized in that, The specific operating steps for the vacuum low-temperature degassing and powder mixing are as follows: First, vacuum the mixture to ≤ Hold at 80-120℃ for 2-5 hours to remove gas, then fill with high-purity argon to positive pressure and mix the powder at 10-30 rpm for 12-24 hours. The conditions for cold isostatic pressing are: pressure 200-400MPa, holding pressure for 5-15min; The conditions for the low-temperature vacuum pre-firing are: temperature 500-580℃, vacuum ≤ Keep warm for 2-5 hours.

9. The method for preparing an in-situ interfacially bonded graphene ultrafine copper bonding wire according to claim 1, characterized in that, The specific operation of the gradient hot isostatic pressing densification is as follows: under the protection of high-purity argon, first hold at 300-350℃ and 50-80MPa for 30-50min, then hold at 500-550℃ and 100-150MPa for 60-80min, and finally hold at 680-720℃ and 150-200MPa for 80-120min; The specific operation of the medium and low temperature hot extrusion is as follows: under high purity pressure protection, preheat at 500-600℃ for 30-50 minutes, and then extrude at 400-500℃ with an extrusion ratio of (10-20):1, with an extrusion outlet bar diameter of 5-10mm. The specific operation of the multi-pass controlled drawing is as follows: the single-pass reduction rate of the drawing is 10-15%, first coarse drawing to a diameter of 1-2 mm, then medium drawing to a diameter of 0.2-0.5 mm, and finally fine drawing to a diameter of 15-30 μm; The specific operation of the stepped low-temperature annealing is as follows: under the protection of high-purity argon, first hold at 150-200℃ for 30-50 min, then hold at 250-300℃ for 60-100 min, and finally hold at 180-220℃ for 30-50 min.

10. An in-situ interfacial bonded graphene ultrafine copper bonding wire, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.

Citation Information

Patent Citations

  • High-strength and high-conductivity graphene copper composite wire and preparation method thereof

    CN112359244A